The Application of the Student Teams Achievement Division (STAD) Cooperative Learning Model on the Ability to Understand the Concept of Elementary School Students - Hardiyanti, Dita (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research is motivated by the importance of students' conceptual understanding ability. However, the ability of students to understand concepts in reality is still low. A STAD type cooperative learning model is applied to overcome these problems. The problem studied is the influence of the ability to understand concepts of elementary school students on social studies learning is reviewed as a whole. This research is a quasi-experimental study with a pre-test-post-test control group design. The research instrument used is a multiple-choice test for understanding social studies concepts. The results showed: 1) There were differences in the pre-test and post-test of students' understanding of social studies concepts in the experimental class that applied STAD-type cooperative learning, 2) There were differences in pre-test and post-test of students' understanding of social studies concepts in the control class that applied TGT-type cooperative learning, 3) STAD-type cooperative learning students outperform TGT-type cooperative learning students in terms of pre-test and post-test understanding of social studies concepts. Based on these results, it can be concluded that cooperative learning type Student Teams Achievement Division (STAD) can improve students understanding of social studies concepts.